2009
DOI: 10.1074/jbc.m109.054528
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the β Clamp in Methyl-directed Mismatch Repair in Vitro

Abstract: We have examined function of the bacterial β replication clamp in the different steps of methyl-directed DNA mismatch repair. The mismatch-, MutS-, and MutL-dependent activation of MutH is unaffected by the presence or orientation of loaded β clamp on either 3′ or 5′ heteroduplexes. Similarly, β is not required for 3′ or 5′ mismatch-provoked excision when scored in the presence of γ complex or in the presence of γ complex and DNA polymerase III core components. However, mismatch repair does not occur in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 48 publications
1
47
0
Order By: Relevance
“…The apparent requirement for mobile MutS-MutL complexes in methyl-directed repair may reflect fundamental differences from MutH-independent repair, such as in Taq and eukaryotes. In particular, early steps in methyl-directed repair are β/PCNA clamp-independent and the MutL homolog lacks endonuclease activity (34), whereas, in MutH-independent repair, MutL has latent endonuclease activity that is activated by β/PCNA at an early step. In the latter system, interactions between β/PCNA clamps, which are loaded onto primer-template DNA junctions in a specific orientation, and MutS-MutL complexes trapped at the mismatch site could direct MutL nicking activity to the nascent strand in the vicinity of the mismatch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent requirement for mobile MutS-MutL complexes in methyl-directed repair may reflect fundamental differences from MutH-independent repair, such as in Taq and eukaryotes. In particular, early steps in methyl-directed repair are β/PCNA clamp-independent and the MutL homolog lacks endonuclease activity (34), whereas, in MutH-independent repair, MutL has latent endonuclease activity that is activated by β/PCNA at an early step. In the latter system, interactions between β/PCNA clamps, which are loaded onto primer-template DNA junctions in a specific orientation, and MutS-MutL complexes trapped at the mismatch site could direct MutL nicking activity to the nascent strand in the vicinity of the mismatch.…”
Section: Resultsmentioning
confidence: 99%
“…Our study also does not rule out the possibility that mobile MutS-MutL signaling complexes may form and complement the functions of stationary MutS-MutL mismatch complexes in DNA repair, e.g., for long-range search of a strand-discrimination signal when one is not available near the mismatch (5,16). In MutH-dependent methyl-directed MMR (as in E. coli), localized assembly of MutS-MutL at the mismatch alone cannot account for orientation-dependent loading of the appropriate 5′-to-3′ or 3′-to-5′ excision system at the nick made by MutH at a d(GATC) site (34), because the mismatch can be up to a kilobase from the break (35) and the helicase loading process must involve signaling along the helix contour. The apparent requirement for mobile MutS-MutL complexes in methyl-directed repair may reflect fundamental differences from MutH-independent repair, such as in Taq and eukaryotes.…”
Section: Resultsmentioning
confidence: 99%
“…The data from B. subtilis and B. anthracis show that MutS interaction with the ␤ clamp is crucial for mismatch repair in some Gram-positive organisms, and it may be found to be important in other organisms that lack a dam-directed repair pathway, although this remains to be established. The involvement of the ␤ clamp in mismatch repair in dam-directed systems such as that of E. coli is unclear and requires further study (221)(222)(223)314). …”
Section: Involvement Of ␤ Clamp In Mismatch Repairmentioning
confidence: 99%
“…Because of the high-affinity interaction between PCNA and MSH6 and MSH3, it had been anticipated that the latter requirement will involve MutSa or MutSb, respectively (Kleczkowska 2001;Shell et al 2007b). However, deletion of the amino-terminal sequences of human MSH6 failed to fully abrogate MMR in vitro, which led to the suggestion that PCNA is required for interactions with members of the mismatch repairosome other than MutSa (Iyer et al 2008;Pluciennik et al 2009). Indeed, follow-up experiments suggested that PCNA is required to activate the latent endonuclease of MutLa.…”
Section: Degradation Of the Error-containing Strandmentioning
confidence: 99%
“…Most replication and repair factors dock with these processivity clamps through highly conserved sequence motifs (Dalrymple et al 2001;Warbrick 2006), and MMR proteins are no exception. The interactions between the polymerase processivity clamps and MSHs are essential for MMR in vivo (Ló pez de Saro et al 2006;Shell et al 2007b;Simmons et al 2008) and in vitro (Pluciennik et al 2009, but what is their function?…”
Section: Degradation Of the Error-containing Strandmentioning
confidence: 99%